A DESCRIPTIVE STUDY OF THE OFFER AS FOUND IN AMERICAN MOVIES - Musadad Musadad (Universitas Gadjah Mada, 2013)
The offer is one form of speech act realizations. Making offer in English belongs to a real example of communicative English learning for it requires practical implementation in some ways. Accordingly, one should not only comprehend the offer in English from what is stated in English grammar books, but also from certain situation providing imaginary life aspects as can be found in the real ones. Such a situation, which is later on called as context, can be displayed through American movies. This study found interesting features in the way the subjects manipulate and manage offers intended to their hearers. The features are mainly noted in three aspects which are utterance length indicating offer (offer-sequence), speech act classification indicating offer, and the most frequently used semantic formulae in accordance with the differences of age, familiarity, and status.